2015
DOI: 10.1111/1440-1630.12194
|View full text |Cite
|
Sign up to set email alerts
|

Identifying educational priorities for occupational therapy students to prepare for mental health practice in Australia and New Zealand: Opinions of practising occupational therapists

Abstract: The priority list developed as part of this project provides additional information to support the review of occupational therapy curricula across Australia and New Zealand to ensure that new graduates are optimally prepared for mental health practice.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
35
1
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 19 publications
(38 citation statements)
references
References 38 publications
(35 reference statements)
1
35
1
1
Order By: Relevance
“…The priorities of Australian and New Zealand occupational therapists for mental health curricula identified in Scanlan et al's (2015) study stand in stark contrast to the priorities of consumers identified in this study. This misalignment is consistent with the concerns raised by Mahboub and Milbourn (2015) in their invited response to Scanlan et al Occupational therapists appear to prioritise occupational therapy professional knowledge and clinical skills as they are applied in a mental health setting.…”
Section: Comparing Occupational Therapists' and Consumers' Prioritiescontrasting
confidence: 87%
See 4 more Smart Citations
“…The priorities of Australian and New Zealand occupational therapists for mental health curricula identified in Scanlan et al's (2015) study stand in stark contrast to the priorities of consumers identified in this study. This misalignment is consistent with the concerns raised by Mahboub and Milbourn (2015) in their invited response to Scanlan et al Occupational therapists appear to prioritise occupational therapy professional knowledge and clinical skills as they are applied in a mental health setting.…”
Section: Comparing Occupational Therapists' and Consumers' Prioritiescontrasting
confidence: 87%
“…Two particular areas of misalignment are engagement in therapy, and risk assessment and management. The idea of the ‘challenging consumer” who is difficult to engage, and the need for risk assessment and management were regarded as essential priorities by occupational therapists in Scanlan et al . 's study.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations